Home preference at selecting financial advisors in cross-border M&As - Bill B. Francis; Iftekhar Hasan; Xian Sun (Bank of Finland, 2012)
This paper examines the determinants of the choice of financial advisors and their impact on the announcement effects of US acquirers in cross-border M&As. Two hypotheses are tested: one pertains to the acquiring firms' home preference in selecting financial advisors, and the other relates to advisors' experience in target countries. Evidence supports the home preference hypothesis in the selection of advisors in cross-border M&As, particularly in all-cash paid transactions where acquirers take the entire risk of not realizing the expected synergy value. We also observe home preference among investors as acquirers that picked US advisors experience significantly higher positive abnormal returns in all-cash paid transactions than those without US advisors, even when the chosen US advisors do not have significant experience in the target country. Finally, home preference at the choice of financial advisor may be costly if US acquirers pass by more experienced because of home preference.
URN:NBN:fi:bof-20140807343
Keywords: 330